2016
DOI: 10.1371/journal.ppat.1005891
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated TGF-β Production Underlies the Age-Related Vulnerability to Chikungunya Virus

Abstract: Chikungunya virus (CHIKV) is a re-emerging global pathogen with pandemic potential, which causes fever, rash and debilitating arthralgia. Older adults over 65 years are particularly susceptible to severe and chronic CHIKV disease (CHIKVD), accounting for >90% of all CHIKV-related deaths. There are currently no approved vaccines or antiviral treatments available to limit chronic CHIKVD. Here we show that in old mice excessive, dysregulated TGFβ production during acute infection leads to a reduced immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 45 publications
(57 reference statements)
2
50
0
Order By: Relevance
“…In experimentally infected macaques, joints, muscles, lymphoid organs, and liver harbor infectious CHIKV or CHIKV RNA for months (18,19). Wild-type (WT) C57BL/6 mice infected with CHIKV develop chronic synovitis (20), and CHIKV RNA and infectious virus can be detected in joint-associated tissue for months (20)(21)(22)(23). The severity of chronic joint disease is increased in aged WT mice with persistent CHIKV infection, and is associated with defects in adaptive immunity (22).…”
Section: Introductionmentioning
confidence: 99%
“…In experimentally infected macaques, joints, muscles, lymphoid organs, and liver harbor infectious CHIKV or CHIKV RNA for months (18,19). Wild-type (WT) C57BL/6 mice infected with CHIKV develop chronic synovitis (20), and CHIKV RNA and infectious virus can be detected in joint-associated tissue for months (20)(21)(22)(23). The severity of chronic joint disease is increased in aged WT mice with persistent CHIKV infection, and is associated with defects in adaptive immunity (22).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we observed that levels of TGF-β expression were reduced in young WT mice infected with MAYV. High levels of TGF-β were associated with a reduced immune response, persistent viremia, and with joint pathology in CHIKV infection in old mice (46). Therefore, the lower levels of TGF-β in MAYV infection could be important to sustain an immune response that restricts muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…The sufficiency of dsRNA to induce arthritis in mice suggests that suppressing immune responses could alleviate post-CHIKV chronic arthralgia and synovitis, which is associated with the presence of vRNA [51,52,5456,58] and persistently elevated type I IFN production [51,55]. Immunosuppressive therapy using methotrexate, corticosteroids, or TNF blockers has shown some efficacy, although not universal, at improving symptoms and limiting progressive joint damage in patients with chronic CHIKV disease [70,71].…”
Section: Viral Pamps - Does Vrna Drive Chronic Disease?mentioning
confidence: 99%